Malay to English signboard converter using augmented reality - Vinayagini, Vijayan (2018)
Signboard information plays an important role in our society. The signboard is often concise and direct, and the information they provide is usually very useful. However, the foreign may not understand the language that the signboard is written in, with the consequent loss of all that important information also they may pose problems or even risk when we are not acquainted with it. For example, foreign might not have the capacity to understand a sign in a foreign country that specifies warnings or hazards. This project is about developed signboard translation application for mobile using augmented reality technology. Augmented reality describes this technology is an enhancement the virtual experience by adding elements of the real environment. This project is basically designed for foreign students, foreign lecturers, and visitors. Using of AR innovation, users can interact with the 3D models and other information provided which existing in the application. This application is generally develop using Autodesk Maya, Android Studio and Unity with Vuforia package. The project development involves Addie approach in building up the application.